FEATURES OF USING DIGITAL EDUCATIONAL RESOURCES IN HIGH SCHOOL - Tulbasova Б.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article defines the components use digital educational resources in secondary schools, in particular, motivationaltarget component of the digital learning; a substantial component of the digital education; operationally-activity component of digital learning; estimating the productive component of digital learning. Their content and problems to be solved in the educational process were determined. In order to teach computer science in the natural-mathematical direction, the e-learning project analyzed digital educational resources operating in several republics. Microsoft Office, Macromedia Flash, Corel Draw, Adobe Photoshop, Ulead GifAnimator, Adobe Premiere series software products, HTML documents, Macromedia DreamWeaver, MS FrontPage and as editing tools Microsoft Power Point, Prezi Desktop, Sway, SlideRocket, Google Docs, Slides 280, Photodex ProShow Producer, features of application of digital educational resources are considered. Keywords: digital educational resource, educational process, MS Power Point, Prezi Desktop, Sway, SlideRocket,